SENSITIVITY OF BCG INOCULATION AND TUBERCULIN SKIN TEST IN ACTIVE PULMONARY TUBERCULOSIS IN UNDER-5 CHILDREN - Muhammad Saleem Channer; Muhammad Saddique Khan Qadri; Ghulam Qasim Khan Khichi (Journal of University Medical & Dental College, 2015)
ABSTRACT OBJECTIVE: To compare the sensitivity of Mantoux test versus BCG inoculation in patients of pulmonary tuberculosis in children up to 5 Years of age. DESIGN: Hospital based study quasi experimental study. PLACE AND DURATION: Study was carried out in Pediatric Medicine Ward in Teaching Hospital of Dera Ghazi Khan Medical College, over a period of two years. SUBJECT AND METHODS: This study was carried out on 100 patients of pulmonary tuberculosis diagnosed according to set criteria. Sample size was calculated by WHO sample size calculator at an absolute precision of 0.08. The sample size was found to be 100. Hence 100 patients suffering from pulmonary tuberculosis were inducted by non probability consecutive sampling technique from February 01, 2013 to February 02, 2015. BCG inoculation and Mantoux test was done on each patient concurrently and their response was studied. RESULTS: Out of 100 patients 56% ware males and 44% females. In 25% of the total cases neither BCG skin test nor Mantoux test showed positive response. Results of the 45 patients were those in which both BCG skin test and Mantoux test were positive: 30 patients (30%) were only BCG skin test positive, so total BCG skin test positive patients were 75%. CONCLUSION: BCG inoculation was far more superior to Mantoux test as diagnostic tool in pediatric age group. Pulmonary tuberculosis study conﬁrmed that BCG skin test was much more sensitive as well as speciﬁc as compared to Mantoux test in the detection of tuberculin allergy in patients suffering from pulmonary tuberculosis.